Human disease locus discovery and mapping to molecular pathways through phylogenetic profiling. Issue 1 (1st October 2013) - Tabach, Yuval; Golan, Tamar; Hernández‐Hernández, Abrahan; Messer, Arielle R; Fukuda, Tomoyuki; Kouznetsova, Anna; Liu, Jian‐Guo; Lilienthal, Ingrid; Levy, Carmit; Ruvkun, Gary
Abstract : Genes with common profiles of the presence and absence in disparate genomes tend to function in the same pathway. By mapping all human genes into about 1000 clusters of genes with similar patterns of conservation across eukaryotic phylogeny, we determined that sets of genes associated with particular diseases have similar phylogenetic profiles. By focusing on those human phylogenetic gene clusters that significantly overlap some of the thousands of human gene sets defined by their coexpression or annotation to pathways or other molecular attributes, we reveal the evolutionary map that connects molecular pathways and human diseases. The other genes in the phylogenetic clusters enriched for particular known disease genes or molecular pathways identify candidate genes for roles in those same disorders and pathways. Focusing on proteins coevolved with the microphthalmia‐associated transcription factor (MITF), we identified the Notch pathway suppressor of hairless (RBP‐Jk/SuH) transcription factor, and showed that RBP‐Jk functions as an MITF cofactor. Abstract : By analyzing the conservation of human proteins across 87 species, we sorted proteins into clusters of coevolution. Some clusters are enriched for genes assigned to particular human diseases or molecular pathways; the other genes in the same cluster may function in related pathways and diseases. Synopsis: By analyzing the conservation of human proteins across 87 species, we sorted proteins into clusters of coevolution. Some clusters are enriched for genes assigned to particular human diseases or molecular pathways; the other genes in the same cluster may function in related pathways and diseases. Many genes that were thought to map to different diseases are actually coevolved together and mapped into the same phylogenetic clusters. Many molecular pathways map to the same phylogenetic clusters as genes associated with specific human diseases. Focusing on proteins coevolved with the microphthalmia‐associated transcription factor (MITF), we identified the Notch pathway suppressor of hairless (RBP‐Jk/SuH) transcription factor, and showed that RBP‐Jk functions as an MITF cofactor. Our analysis thus establishes a connectivity between different diseases and pathways, linking diseases phenotypes and functional gene groups.